Cryptography and secure communication - Blahut, Richard E. (Cambridge : Cambridge University Press, 2014)
Today's pervasive computing and communications networks have created an intense need for secure and reliable cryptographic systems. Bringing together a fascinating mixture of topics in engineering, mathematics, computer science, and informatics, this book presents the timeless mathematical theory underpinning cryptosystems both old and new. Major branches of classical and modern cryptography are discussed in detail, from basic block and stream cyphers through to systems based on elliptic and hyperelliptic curves, accompanied by concise summaries of the necessary mathematical background. Practical aspects such as implementation, authentication and protocol-sharing are also covered, as are the possible pitfalls surrounding various cryptographic methods. Written specifically with engineers in mind, and providing a solid grounding in the relevant algorithms, protocols and techniques, this insightful introduction to the foundations of modern cryptography is ideal for graduate students and researchers in engineering and computer science, and practitioners involved in the design of security systems for communications networks.
Contents note continued: 3.3.Protocol attacks on biprime cryptography -- 3.4.Direct attacks on biprime encryption -- 3.5.Factoring biprimes -- 3.6.The quadratic sieve -- 3.7.The number-field sieve -- 3.8.The Rabin cryptosystem -- 3.9.The rise and fall of knapsack cryptosystems -- 4.Cryptography based on the discrete logarithm -- 4.1.Diffie--Hellman key exchange -- 4.2.Discrete logarithms -- 4.3.The Elgamal cryptosystem -- 4.4.Trapdoor one-way functions -- 4.5.The Massey--Omura cryptosystem -- 4.6.The Pohlig--Hellman algorithm -- 4.7.The Shanks algorithm -- 4.8.The Pollard algorithm for discrete logarithms -- 4.9.The method of index calculus -- 4.10.Complexity of the discrete-log problem -- 5.Information-theoretic methods in cryptography -- 5.1.Probability space -- 5.2.Entropy -- 5.3.Perfect secrecy -- 5.4.The Shannon--McMillan theorem -- 5.5.Unicity distance -- 5.6.Entropy of natural language -- 5.7.Entropy expansion -- 5.8.Data compaction -- 5.9.The wiretap channel --
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Data encryption (Computer science); Cryptography; Telecommunication -- Security measures